Use of nutritional supplement to improve performance in professional soccer players: A case report - Messina, G.; Francavilla, V. C.; Giustino, V.; Mingrino, O.; Genovesi, F.; Amato, A.; Proia, P. (Journal of Human Sport & Exercise, 2020)
The aim of the study was to investigate the intake percentage and the satisfaction level of some nutritional supplements used by professional soccer players. Twenty-nine professional soccer players (age: 24.6 ± 5.2 years, body weight: 79.2 ± 4.9 kg, body height: 1.83 ± 0.05 m) belonging to a team of Serie A were interviewed on: frequency of use, tolerability, and acceptance of the supplements (creatine, ß-alanine, whey protein, nitrates, vitamin D3, caffeine) proposed by the nutritionist team. This survey revealed a great inter-individual variability on the intake of the proposed supplements. All respondents (n = 29) said they take cholecalciferol (vitamin D3), 17 out of 29 creatine, 14 out of 29 whey protein, and 10 out of 29 dietary nitrates. No participants declared to assume ß-alanine or caffeine anhydrous. Cholecalciferol resulted the most accepted supplement, followed by creatine and whey protein. Study participants prefer to take dietary nitrates through the consumption of vegetable juices, primarily from fennel and celery juice, and only two out of twenty-nine regularly taking concentrated beet juice. Since none of the twenty-nine participants interviewed uses ß-alanine and caffeine in anhydrous form, the daily contribution of caffeine is mainly guaranteed by the consumption of coffee.